Risk Perception, Behavior Change and Perceived Impact due to COVID-19 Pandemic among General Population in Tamil Nadu, India: A Cross-Sectional Study - Hemalatha Kumarasamy; Prabha Thangaraj (Shahid Sadoughi University of Medical Sciences, 2023)
Background: Coronavirus disease 2019 (COVID-19) has affected countries all over the world. Assessment of risk perception and scaling up appropriate behavioral practices are of utmost importance for its prevention and control. The objectives of this study were identifying risk perception, behavioral changes and perceived impact as a result of COVID-19 and its associated factors among general population. Methods: A cross-sectional study was done during the first wave of COVID-19 among general population in Tamil Nadu, India. A semi-structured questionnaire was prepared in Google forms and circulated using WhatsApp during April and June 2020. The sample size was calculated at 384. Data were analyzed using SPSS software version 21.0. Association between the variables was analyzed using Chi-square test. P-value <0.05 was considered significant.  Results: Mean age was 38.4 ±13.8, and 52.1% of the participants were females. Almost 2/3rdhad perceived risk of catching COVID-19, which was more among respondents aged 20-39 and residing in urban area. Among the behavior change measures, wearing mask in public places was practiced by 95%, followed by hand washing (90.4%) and social distancing (80%). More than 50% had some form of psychological stress that included inability to perform their daily routines, anxiously browsing media for information about COVID-19, not going to work .etc. Conclusion: General public staying in rural areas have not completed secondary school education, and the elderly have to be targeted to provide appropriate information about COVID-19 and its preventive measures.